Pengaruh Lingkungan Sekolah terhadap Pertumbuhan Iman dan Moral Siswa Kristen - Fictor M.Dethan; Marniati Tanesab; Melki Manu; Yuninggsi Pehejes (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
This study aims to analyze the influence of the school environment on the growth of faith and morality among Christian students at Elpida Senior High School Noelbaki. The research is based on the premise that a Christian school is not merely an institution for knowledge transfer, but also a formative environment for spiritual and moral development. The study employed a quantitative approach with a survey method. The population included all students of Elpida Senior High School Noelbaki, while the sample consisted of 80 purposively selected students. The research instrument was a five-point Likert scale questionnaire covering spiritual, social, and academic aspects of the school environment. Data were analyzed using simple linear regression to determine the effect of the school environment on students’ faith and moral growth. The results revealed that the school environment has a positive and significant influence on students’ spiritual and moral development (t = 5.36, p < 0.05). A Christian-based school environment encourages students to live in obedience, love, and responsibility toward others. This study concludes that faith and moral education are not only taught theoretically but also modeled through school culture, teacher-student relationships, and a spiritually nurturing atmosphere.